Reconfiguring Islamic Authority in Indonesia: The Role of Ulama and Digital Media in Religious Practices - Anam Besari; Vicheka Rith; Ravi Dara (Journal of Noesantara Islamic Studies, 2025)
The digital revolution has profoundly reshaped the landscape of religious authority and practice in the Muslim world, challenging traditional clerical hierarchies. In Indonesia, the authority of the ulama, long central to the dissemination of Islamic knowledge, now coexists with a vibrant and often unregulated digital sphere. This study aimed to investigate how digital media is reconfiguring traditional Islamic authority and influencing the religious practices of Indonesian Muslims. The primary objective was to analyze the strategies employed by both traditional ulama and new digital religious figures in this evolving media ecosystem. A qualitative methodology was employed, combining digital ethnography of popular religious social media platforms with in-depth, semi-structured interviews with established ulama and emergent "cyber-preachers." The results reveal a significant fragmentation and democratization of religious authority. New media figures are leveraging platforms like YouTube and Instagram to bypass traditional institutions, offering direct religious guidance to a mass audience. In response, many traditional ulama are adapting by creating their own digital presence, yet often struggle to match the popular appeal of these new influencers. This study concludes that digital media is fostering a more contested, personalized, and networked religious landscape in Indonesia. This reconfiguration is not replacing the traditional ulama but is forcing them into a new, competitive role, fundamentally altering how religious authority is constructed, consumed, and maintained in the digital age.